2013 11th IEEE International Conference on Industrial Informatics (INDIN) 2013
DOI: 10.1109/indin.2013.6622954
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and prediction of jitter of internet one-way time-delay for teleoperation systems

Abstract: Abstract-Internet random time delay constitutes a major challenge for Internet-based teleoperation systems. Since the uncertain time delay may degrade the system performance, and even lead to instability. Although large-scale research works have been conducted on the understanding, testing, and analysis of Internet round trip time delay (RTT), it is not appropriate to use RTT in control methods design. It is well known that control commands arrive at the slave site in an aperiodic manner as a result of Interne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Finally, denotes the sum . As introduced in [6] and also confirmed in a recent study [26], Internet packet delay is modeled as shifted Gamma distribution. In such a case, is given by:…”
Section: A Network Modelmentioning
confidence: 69%
“…Finally, denotes the sum . As introduced in [6] and also confirmed in a recent study [26], Internet packet delay is modeled as shifted Gamma distribution. In such a case, is given by:…”
Section: A Network Modelmentioning
confidence: 69%
“…In the implementation presented in this paper, only three prediction algorithms are tested, but any methods that satisfy real time requiremet and precision can conceivably be used. In our previous works [23], an initial study indicated that there were structured information in Internet jitter data. However, extensive works should be conducted to study the characteristics of Internet OWTD jitter data.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, characteristics of Internet OWTD jitter should be analyzed and prediction methods should be selected appropriately. In our previous works [23], an initial analysis has been performed and the results indicate that relative correlation between jitter data arrays exist, as shown in Fig. 3.…”
Section: Prediction Methods Of Internet Owtd Jittermentioning
confidence: 98%
“…Telebot also uses the internet to test different forms of control [138]. Issues with Internet-based teleoperation include variable time-delay (or jitter) [139,140,141,142] and data loss [141,143]. One solution is to use an action reference other than time (i.e.…”
Section: Teleoperationmentioning
confidence: 99%
“…In [142], the authors attempt to analyze and predict the jitter associated with one-way time-delay for teleoperation systems. The problem with jitter is that it means control messages will get to the robot in an aperiodic way and thus terminate current commands in a delayed way.…”
Section: Communication Channel For Teleoperationmentioning
confidence: 99%